Acute Appendicitis Associated With Typhoid Fever: A Case Report and Review of Literature - Sanaz Mehrabani (Mazandaran University of Medical Sciences, 2020)
Introduction: Appendicitis could be a rare complication of Salmonella Typhi infection.  Case Presentation: we present a 13-year-old girl with typhoid fever with histology-proven acute appendicitis as a rare complication of Salmonella Typhi infection. The patient was admitted to the hospital with the chief complaints of fever, abdominal pain, diarrhea, and vomiting for more than one week. A brief review of relevant literature was also performed to explore more this rare cause of a common emergency surgical procedure.  Conclusions: In all cases with typhoid fever with persistent diarrhea and vomiting, localized abdominal pain, probable acute appendicitis should be considered as an important complication.